Evidence for first-order orthorhombic-tetragonal and nearly tricritical tetragonal-cubic antiferrodistortive phase transitions in Ca0.43 Sr0.57 TiO3 - Mishra S.K.; Pandey D. (My University, 2025)
Temperature dependence of the symmetry-adopted strains (secondary order parameter) associated with the antiferrodistortive-phase transitions involving change in space groups from Pm 3̄ m to I4/mcm and I4/mcm to Pnma in Ca0.57 Sr0.43 TiO3 have been investigated using powder x-ray diffraction data in the temperature range of 300-950 K. It is argued that the experimentally determined critical exponent β∼0.33±0.03 in the temperature range 0.70≤T≤0.98 Tc for the I4/mcm to Pm 3̄ m transition is due to a nearly tricritical transition. The Pnma to I4/mcm transition is unambiguously identified as first order. © 2009 The American Physical Society.